A Review on Anti-urease Potential of Coumarins - Asghar, Humna; Asghar, Hafsa; Asghar, Tanzeela (Current Drug Targets, 2021)
Coumarins, a heterocyclic benzo-α-pyrones and naturally occurring ring structure that possess significant pharmacological properties, have attracted the attention of researchers and medicinal chemists to reveal the suitability of both natural and synthetic coumarins as drugs. Many compounds have been synthesized utilizing the basic coumarin structure. The diverse synthetic methods resulted in the synthesis of important coumarin derivatives that offer a wide range of biological properties as antimicrobial, anticancer, anti-inflammatory, antioxidant, antidiabetic and antidepressant that make them potential drug candidates. With a particular interest in ulcers, coumarins have shown potential inhibition against urease enzyme. In recent years, scientists have emphasized the anti-urease activity of coumarins due to their low toxicity. The aim of this review is to compile data from recent research about anti-urease activities of coumarins and structure-activity relationship studies of the coumarin ring structure. Investigation of different structural substitutions in coumarin rings may help researchers to design new compounds with strong and effective anti- urease abilities.
Keywords: jack bean urease